Robotic Arm Rehabilitation in Chronic Stroke Patients With Aphasia May Promote Speech and Language Recovery (but Effect Is Not Enhanced by Supplementary tDCS) - Buchwald, Adam; Falconer, Carolyn; Rykman-Peltz, Avrielle; Cortes, Mar; Pascual-Leone, Alvaro; Thickbroom, Gary W.; Krebs, Hermano Igo; Fregni, Felipe; Gerber, Linda M.; Oromendia, Clara; Chang, Johanna; Volpe, Bruce T.; et al. (Frontiers in Neurology, 2018)
Objective: This study aimed to determine the extent to which robotic arm rehabilitation for chronic stroke may promote recovery of speech and language function in individuals with aphasia. Methods: We prospectively enrolled 17 individuals in a robotic arm rehabilitation study and evaluated their speech and language performance before and after a 12-week (36 session) arm treatment regimen. Performance changes were evaluated with paired t-tests comparing pre- and post-test measures. There was no speech therapy included in the treatment protocol. Results: Overall, the individuals significantly improved on measures of motor speech production as well as overall aphasia severity from pre-test baseline to post-test. Conclusions: This work indicates the importance of considering approaches to stroke rehabilitation across different domains of impairment, and warrants additional exploration of the possibility that robotic arm motor treatment may enhance rehabilitation for speech and language outcomes.